2018
DOI: 10.1016/j.microc.2018.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ruthenium(II) complex-based luminescence probe for detection of hydrogen sulfite in food samples

Abstract: Development of new methods for rapid and effective detection of hydrogen sulfite is of great importance in the studies of this species in food samples. In this contribution, a ruthenium(II) complex-based luminescence probe, Ru-CHO, was developed for fast, highly sensitive and selective recognition and detection of hydrogen sulfite. Ru-CHO was found to be weakly luminescent due to the intramolecular charge transfer dominated by the strong electron withdrawing aldehyde groups. In the presence of hydrogen sulfite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In a later study, Zhang et al found that the nucleophilic addition of aldehyde can also be triggered by hydrogen sulfite (HSO 3 − ) in acidic buffer [ 24 ], thus allowing complex 9 to be used as a chemosensor for HSO 3 − detection in phosphate-buffered saline (PBS) buffer (50 mM, pH = 5) (Fig. 7 ) [ 101 ]. The reaction of HSO 3 − and complex 9 led to the formation of 9-SO , accompanied by an increase of luminescence at 620 nm.…”
Section: Ru(ii) Complex Chemosensors For Anionsmentioning
confidence: 99%
“…In a later study, Zhang et al found that the nucleophilic addition of aldehyde can also be triggered by hydrogen sulfite (HSO 3 − ) in acidic buffer [ 24 ], thus allowing complex 9 to be used as a chemosensor for HSO 3 − detection in phosphate-buffered saline (PBS) buffer (50 mM, pH = 5) (Fig. 7 ) [ 101 ]. The reaction of HSO 3 − and complex 9 led to the formation of 9-SO , accompanied by an increase of luminescence at 620 nm.…”
Section: Ru(ii) Complex Chemosensors For Anionsmentioning
confidence: 99%
“…7 Molecular structures of Ru(II) complexes 9 and 10 and their reactions with HSO 3 − and CN − , respectively thus allowing complex 9 to be used as a chemosensor for HSO 3 − detection in phosphate-buffered saline (PBS) buffer (50 mM, pH = 5) (Fig. 7) [101]. The reaction of HSO 3 − and complex 9 led to the formation of 9-SO, accompanied by an increase of luminescence at 620 nm.…”
Section: Response Based On Specific Reactionsmentioning
confidence: 99%
“…Several theoretical studies have already been performed regarding the chemical issues in foods and their processes. Serobatse and Kabanda have performed a theoretical study on the antioxidant properties of two chalcone derivatives, that is, kanakugiol and pedicellin, toward the ability to coordinate with Fe­(II) and Fe­(III). Medine et al have experimentally and theoretically studied the structures and antimutagenic effects of vanadium with chelating flavonoids.…”
Section: Introductionmentioning
confidence: 99%